Development of a differentiating of infected from vaccinated animal (DIVA) ELISA to detect antibodies against Senecavirus A in pigs using two expression systems of non-structural proteins - Parin Watcharavongtip; Patumporn Jermsutjarit; Angkana Tantituvanont; Dachrit Nilubol (Veterinary Quarterly)
Senecavirus A (SVA) is the causative agent associated with porcine idiopathic vesicular disease (PIVD), a condition indistinguishable from other foreign vesicular diseases affecting pigs. This complicates differential diagnosis and impacts the global swine industry. A diagnostic ELISA based on a non-structural viral protein has been developed, capable of distinguishing infected from vaccinated animals (DIVA). Different expression systems (eukaryotic and prokaryotic) were used to express recombinant proteins. The baculovirus-expressed SVA 3AB DIVA ELISA demonstrated a sensitivity of 96.67% and specificity of 96.67%. In contrast, the E. coli-expressed SVA 3AB DIVA ELISA achieved 100% sensitivity and 93.33% specificity. Both ELISAs strongly correlated with the reference method and showed no cross-reactivity with other pig pathogens. The E. coli system also provided a higher yield of expressed protein than the baculovirus system. These findings indicate that SVA DIVA ELISAs are effective alternatives for detecting SVA antibodies. They can be valuable tools for sero-surveillance and for evaluating immunity status tests to support and approve vaccination programs for pig herds in the future.